PARASITISASI Leefmansia bicolor TERHADAP TELUR Sexava nubila STAL. (ORTHOPTERA;TETTIGONIDAE) PADA TANAMAN KELAPA DI PULAU SALIBABU KABUPATEN KEPULAUAN TALAUD - Alan Lalisang; Betsy A.N. Pinaria; Moulwy F. Dien; Caroulus S. Rante (Universitas Sam Ratulangi, 2015)
ABSTRACTThe study aims to determine the type of potential on the egg parasitoid S. nubila Salibabu Island, Talaud Islands. The experiment was conducted at the coconut plantation owned by farmers on the Salibabu island, Talaud Islands for 4 months ie from October 2014 through January 2015. Research using survey method in 4 districts, namely: (1) District of Salibabu, (2) District of Kalongan, (3) District of Lirung, and (4) District of Moronge. Each district is determined three sampling sites. Research using survey method in 4 districts, namely: (1) District of Salibabu, (2) District of Kalongan, (3) District of Lirung, and (4) District of Moronge. Each district is determined three sampling sites.Sampling method diagonal slices so that at each sample location consists of 5 sub-location. Searches conducted around the egg sample rod with a diameter of 0.5 meters and divide the four sectors/regions observations in the Northern, Eastern, Southern and Western. Sampling was carried out 6 times with intervals twice a month.The results showed that of the eggs samples were infected found only one type of parasitoids. Identification results showed that the parasitoid is Leefmansia bicolorObservations of the eggs percentage of parasitization byL. bicolor in Salibabu island turns found in sub-district of Lirung highest, reaching an average of 26.54%, then successively sub-district of Moronge 17.68%, sub-district of Kalongan 13.03% and sub-district Salibabu 4.20%.The average percentage of parasitisasi based on the direction of the wind turns the highest found in the Eastern sector/Region (32.35%), then the western sector (13.39%), South sector (10.25%) and North (5.45 %)Key words : Parasitization, Sexava nubila, Leefmansia bicolor, Salibabu-Talaud